The long‐term effect of prenatal progesterone treatment on child development, behaviour and health: a systematic review. (28th November 2020) - Simons, NE; Leeuw, M; van't Hooft, J; Limpens, J; Roseboom, TJ; Oudijk, MA; Pajkrt, E; Finken, MJJ; Painter, RC
Abstract : Background: Progesterone is widely used in prenatal care. However, long‐term effects of prenatal progesterone treatment on child development are unclear. Objectives: To evaluate long‐term outcomes in children after prenatal progesterone treatment. Search strategy: MEDLINE, Embase and Cochrane Central Register of Controlled Trials from inception to 24 May 2020. Selection criteria: Randomised controlled trials (RCTs) reporting outcomes in children born to women who received progesterone treatment (compared with placebo or another intervention) during any trimester in pregnancy. Data collection and analysis: Two authors independently selected and extracted data. We used the Cochrane Risk of Bias tool for randomised trials and Quality In Prognosis Studies. Main results: Of 388 papers, we included seven articles based on five RCTs, comprising 4222 measurements of children aged 6 months to 8 years. All studies compared progesterone to placebo in second and/or third trimester for the prevention of preterm birth. Meta‐analysis (two studies, n  = 890 children) showed no difference in neurodevelopment as assessed by the Bayley‐III Cognitive Composite score at 2 years between children exposed to progesterone versus placebo (Standardised Mean Difference −0.04, 95% Confidence Interval −0.26 to 0.19), I 2  = 22%. Heterogeneity prohibited additional meta‐analyses. Other long‐term outcomes showed no differences. Conclusions: Our systematic review comprising a multitude of developmental measurements with a broad age range did not find evidence of benefit or harm in offspring prenatally exposed to progesterone treatment for the prevention of preterm birth. We identified an urgent need for follow‐up studies of prenatal progesterone administration in early pregnancy and effects in offspring beyond early childhood. Tweetable abstract: Progesterone to prevent preterm birth: no effect on child development. Outcomes after first trimester progesterone are unclear. Tweetable abstract: Progesterone to prevent preterm birth: no effect on child development. Outcomes after first trimester progesterone are unclear.